Cryptogenic stroke and patent foramen ovale: endeavoring for clarity - Amini, Tohid (Frontiers in Neurology, 2025)
This review aims to summarize current knowledge and highlight recent findings on the association between cryptogenic stroke (CS) and patent foramen ovale (PFO). By presenting sometimes conflicting data, the review underscores the necessity for further research to clarify the complex mechanisms behind PFO-related CS and optimize its management. Results from research identifies specific conditions and scores, such as the risk of paradoxical embolism (RoPE) score, that help assess the likelihood of PFO-related cryptogenic stroke and guide treatment decisions. PFO closure has demonstrated substantial benefits in select cases, especially those with high-risk PFO features, though complications such as atrial fibrillation were frequently documented. Biomarker measurements, such as reduced total homocysteine (tHcy) level after PFO closure or high D-dimer levels indicating a higher risk of stroke recurrence, represent newer areas of study with a promising future in medical practice. Cryptogenic stroke (CS) remains a diagnostic challenge. This article reviews the current understanding of PFO-related CS, focusing on the interplay of concomitant pathological conditions, PFO closure, stroke recurrence, and some of the related biomarkers.